Welfare Criteria, Pricing and Decentralization of a Public Service - Margolis, Julius (Quarterly Journal of Economics, 1957)
Introduction, 448. — I. Alternative pricing policies, 449. — II. Actual pricing practices and possibilities of introducing an efficient scheme, 453. — III. Requirement of financial feasibility and efficient pricing possibilities, 459. — IV. Conclusion, 462.